Analysis of complications induced by iodine-based radiographic contrast media and of methods of their prevention (А literature review) - Liudmyla Kolotova; Hanna Romanenko; Michael Tkachenko (Bogomolets National Medical University, 2021)
The existence of modern medical practice is impossible without the use of radiological diagnostic methods. Due to the introduction of evidence-based medicine, most diagnoses need to be confirmed by imaging techniques, and some diseases require radiographic contrast media. Despite the medical and scientific breakthrough in these technologies, there are still risks of developing an individual body reaction to the contrast agent. In view of this, the purpose of the work was to substantiate the choice of iodine-containing radiographic contrast agents, to study the possible complications caused by these substances during the X-ray examination, and the methods of prevention of such conditions. To determine these key points, an analytical review of the literature was conducted. Analysis of iodine-containing radiographic contrast agents, which differ in their chemical structure and properties, showed the advantage of non-ionic radiographic contrast media over the ionized ones. The work considers hypersensitive reactions and thyroid dysfunctions caused by the introduction of iodine-containing contrast agents. The allergic reactions may occur occur regardless of the dose of the drug, immediately or after some time after the examination. Due to the fact that the average duration of radiographic examination is from a few minutes to an hour, the appearance a certain reaction to iodine-containing radiographic contrast agents in a patient may not be established in time. That is why, it important to monitor a patient in the radiology department for 30 minutes after the examination. When establishing an increased risk of hypersensitivity reactions, due to the collection of anamnesis, it is necessary to carry out premedication with glucocorticoids is recommended according to the scheme that is described in the literature and is used in the modern medical practice. The development of hyperthyroidism or hypothyroidism depends on the initial level of hormones and the correct operation of the response system. In the presence of anamnestic and laboratory risk factors that can cause the occurrence of these conditions (TSH, free T4, total T3 and Thyroid peroxidase antibodies), it is recommended to consult an endocrinologist and, based on his/her judgement, to carry out premedication with the control of the TSH levels according to the schemes presented in the literature review or, alternatively, to correct the existing pathological conditions before the examination.